1997
DOI: 10.1038/bjc.1997.530
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral bioavailability of paclitaxel in mice treated with the P-glycoprotein blocker SDZ PSC 833

Abstract: Summary Inhibition of intestinal P-glycoprotein might enhance the absorption of orally administered P-glycoprotein substrate drugs. We show here a 10-fold increased oral bioavailability of paclitaxel in mice treated with the P-glycoprotein blocker SDZ PSC 833. These results encourage further research on the development of a clinically useful oral formulation of paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(79 citation statements)
references
References 15 publications
1
77
0
1
Order By: Relevance
“…Studies in mice revealed that coadministration of SDZ PSC833, a cyclosporin D analogue and potent P-gp inhibitor, with paclitaxel resulted in a 10-fold increase in systemic exposure [103]. A similar study was performed with CsA and paclitaxel that has shown comparable effects [104].…”
Section: Paclitaxelmentioning
confidence: 99%
“…Studies in mice revealed that coadministration of SDZ PSC833, a cyclosporin D analogue and potent P-gp inhibitor, with paclitaxel resulted in a 10-fold increase in systemic exposure [103]. A similar study was performed with CsA and paclitaxel that has shown comparable effects [104].…”
Section: Paclitaxelmentioning
confidence: 99%
“…In human, CYP3A4 is the principal enzyme involved in the hepatic and intestinal drug metabolism, and there is a striking overlap of substrate specificites among CYP3A4, P-gp and MRPs. The coordinated function of both CYP3A and P-gp, MRPs can dramatically lower oral bioavailability of compounds which are substrates for both (van Asperen et al, 1997;Wacher et al, 1998) and this may also be true for LVR. P-gp mediated efflux of LVR has been published (Vishnuvardhan et al, 2003;Woodahl et al, 2005) but interactions of LVR with other adenosine triphosphate-binding cassette (ABC) efflux transporters such as MRPs and BCRP have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These properties of paclitaxel create expectations that paclitaxel could be a good therapeutic agent in the treatment of brain tumors. But as paclitaxel is one of the P-gp substrates (21)(22)(23), it cannot reach tumor cells in the brain parenchyma (24), which makes it hard to absorb orally administered paclitaxel from the gut lumen (15). Therefore, inhibition of P-pg activity is essential.…”
Section: Introductionmentioning
confidence: 99%